Heart rate variability evaluation of Emfit sleep mattress breathing categories in NREM sleep. Issue 5 (May 2015) - Tenhunen, Mirja; Hyttinen, Jari; Lipponen, Jukka A.; Virkkala, Jussi; Kuusimäki, Sonja; Tarvainen, Mika P.; Karjalainen, Pasi A.; Himanen, Sari-Leena
Highlights The periodic obstructive breathing detected by the Emfit mattress induces similar effects on autonomous nervous system as sleep apnea. Instead, during the sustained partial obstruction sympathetic activity did not increase but parasympathetic activity increased. Sustained partial obstruction seems to be a distinct entity differing from sleep apnea.